UJI BEBERAPA KONSENTRASI TEPUNG BIJI PINANG (Areca catechu L.) TERHADAP MORTALITAS LARVA PENGGEREK TONGKOL JAGUNG MANIS (Helicoverpa armigera Hubner) - Arohma Yuli Murtika Dewi; Desita Salbiah; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The using synthetic chemical insecticide to continue and not prudently can be to come negative effect. So, to needed alternative controlling technic like as insecticide botanic. Insecticide botanic such as betel nut seed powder. Research aims to found a concentration of betel nut seed powder (Areca catechu L) wich is appropriate to killed sweet corn cob borer (Helicoverpa armigera Hubner). This research was conducted in the Laboratory of Plant Pests Agricultural Faculty University of Riau using a completely randomized design (CRD) with 5 treatments and 4 replications. The treatment will be used is the concentration of betel nut powder 0 g / l water, 30 g / l water, 40 g / l  water, 50 g / l water, 60 g / l water. The result showed concentration betel nut seed powder 50 g / l water is able to kill the larvae of   H. armigera is much as 90%. Key Words : betel nut seed  (Areca catechu L), sweet corn cob borer (Helicoverpa armigera Hubner), insecticide